Differential interactions of human choriogonadotropin and its antagonistic aglycosylated analog with their receptor. - Ji, I (1990)
Human choriogonadotropin (hCG) is a heterodimeric hormone consisting of an alpha subunit and a beta subunit. hCG and aglycosylated hCG (aghCG) have similar receptor binding affinities but differ in their ability to activate hormone-responsive adenylate cyclase. aghCG is an effective antagonist. The mechanisms of this antagonism and interactions of antagonistic aghCG with the receptor are not understood. To address this critical question, we have examined the interaction of this hormone analog with the receptor. The hormone receptor on porcine granulosa cells is a glycoprotein of 86 kDa and thas three domains of 24 kDa, 28 kDa, and 34 kDa, which are disulfide-linked. They undergo proteolysis, particularly when bound to the hormones, to produce three polypeptide components. These three receptor components can readily be identified through the use of affinity labeling with the hormones. Affinity labeling with an amino-specific homobifunctional reagent and subsequent cleavage indicate that hCG is cross-linked directly to the 24-kDa receptor component. In contrast, aghCG is cross-linked directly to the 34-kDa component. The peptide map of the cross-linked aghCG-34-kDa receptor component produced by papain treatment is different from the peptide map of the cross-linked complex of hCG-24-kDa component. This difference in receptor binding may be a factor determining the success or failure of signal transduction from the receptor to the effector system, guanine nucleotide-binding regulatory protein, and adenylate cyclase.